2023
DOI: 10.3390/idr15010006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Patients Hospitalized with ST-Segment Elevation Myocardial Infarction in the United States during the Early Pandemic: An Analysis of Outcomes, Care Delivery, and Racial Disparities in Mortality

Abstract: The COVID-19 pandemic has impacted healthcare delivery to patients with ST-segment elevation myocardial infarction (STEMI). The aim of our retrospective study was to determine the effect of COVID-19 on inpatient STEMI outcomes and to investigate changes in cardiac care delivery during 2020. We utilized the National Inpatient Sample database to examine inpatient mortality and cardiac procedures among STEMI patients with and without COVID-19. In our study, STEMI patients with COVID-19 had higher inpatient mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The finding that 3% of hospital admissions with a diagnosis of STEMI had additional analysis of COVID-19 is important. Similar finding in the analysis that was focused on STEMI admissions and concomitant COVID-19 disease in NIS database for the year 2020, reported similar prevalence of COVID-19 in their cohort which was 3.4%, a result similar to ours thus validating our findings [12].…”
Section: Discussionsupporting
confidence: 92%
“…The finding that 3% of hospital admissions with a diagnosis of STEMI had additional analysis of COVID-19 is important. Similar finding in the analysis that was focused on STEMI admissions and concomitant COVID-19 disease in NIS database for the year 2020, reported similar prevalence of COVID-19 in their cohort which was 3.4%, a result similar to ours thus validating our findings [12].…”
Section: Discussionsupporting
confidence: 92%
“…Existing research strongly suggests that COVID‐19 infection worsens the outcomes of various cardiovascular diseases, including myocardial infarctions and acute ischemic strokes, with patients infected with COVID‐19 experiencing significantly higher mortality rates. 15 , 16 , 17 , 18 Furthermore, during the pandemic, preventive measures potentially affected acute ischemic stroke management, leading to treatment delays and subsequently influencing early adverse outcomes in patients with acute ischemic stroke. 19 However, the impact of COVID‐19 on hemorrhagic stroke, specifically ICH, is less well studied and primarily derived from smaller, single‐center studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalizations and mortality for other respiratory infections were significantly decreased during the pandemic ( 31 ). The effect of COVID-19 on STEMI ( 32 ) and stoke ( 33 ) outcomes have also been demonstrated, resulting in higher in-patient mortality, length of stay and cost of hospitalization. Kapuria et al found that patients with COVID-19 and cirrhosis had 3 times higher mortality than those without COVID-19 ( 34 ) and Pal et al found sex and racial disparities in hospitalizations and in rates of adverse outcomes ( 35 ).…”
Section: Discussionmentioning
confidence: 99%